Opinion Analysis of Traveler Based on Tourism Site Review Using Sentiment Analysis - Amira, Siti Azza; Irawan, M. Isa (IPTEK The Journal for Technology and Science, 2020)
Technology development nowadays makes it easier for people to access information. One of them is to find information regarding a place. Many prospective visitors would read reviews from people who have visited a place to find out how they rate a place. Opinion on other people’s reviews is very influential in influencing others’ decisions in assessing a place they want to visit. Opinion analysis can be done by conducting a sentiment analysis of hotel customer reviews. The data used are traveler reviews of hotels in East Java on the Tripadvisor site. Traveler reviews data was taken by crawling on tourist sites, and the unstructured reviews data would be a preprocessing and weighted term from reviews using the TF-IDF method. The classification process is done using the support vector machine method to find opinions from traveler reviews, which are positive or negative. Based on the classification results, hotels that have the most positive sentiments in Surabaya are Harris Hotel Gubeng and Pop! Hotel Gubeng with the same number of reviews, 252 reviews. In comparison, hotels with the most positive sentiment in Malang are Harris Hotel Malang with 311 reviews. The opinion analysis results are expected to help the hotel manager evaluate and develop to increase the number of tourist visits.